Analisis Ketepatan Sasaran Program 35 Ribu Mega Watt Untuk Indonesia Menggunakan Metode Exponential Smoothing - Desty Rakhmawati; Hendra Marcos (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2018)
PT PLN (Persero) electricity customers consist of household, industry, social, business and public customer groups. The amount of electricity distributed per customer varies. The amount of electricity in 2016 until 2019, will be distributed to increase the electricity supply of household, industry, and non-powered groups of electricity. This refers to the target of 35 thousand MW program for Indonesia. It is according to the accuracy of the program's objectives. The purpose to see this program ,so this research to analyze data on the amount of electricity distributed to household, industry and public customer groups. Data analysis was doing with exponential smoothing method, and then using optimum parameters. This resulted prediction value of the amount of electricity distributed from 2016 until 2025. Then based on the prediction result, give an analysis showing that the accuracy of the target of 35 thousand MW program.